Deep learning algorithm to detect tree defects via circular scans - Nguyen, Thanh Tin (Nanyang Technological University, 2024)
This research aims to advance the accuracy and efficiency of tree defect detection and analysis by integrating Ground-penetrating Radar (GPR) with Deep Learning techniques. It delves into discussions on GPR-based techniques, circular scanning methods for tree imaging, and the application of Convolutional Neural Network (CNN) for deep learning.